2020
DOI: 10.1007/s10875-019-00737-x
|View full text |Cite|
|
Sign up to set email alerts
|

Human Inborn Errors of Immunity: 2019 Update on the Classification from the International Union of Immunological Societies Expert Committee

Abstract: We report the updated classification of Inborn Errors of Immunity/Primary Immunodeficiencies, compiled by the International Union of Immunological Societies Expert Committee. This report documents the key clinical and laboratory features of 430 inborn errors of immunity, including 64 gene defects that have either been discovered in the past 2 years since the previous update (published January 2018) or were characterized earlier but have since been confirmed or expanded upon in subsequent studies. The applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
993
1
54

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 984 publications
(1,122 citation statements)
references
References 105 publications
8
993
1
54
Order By: Relevance
“…A molecular study found that HIES is caused by variations in STAT3, Dedicator of cytokinesis 8 (DOCK8) [28], phosphoglucomutase 3 gene (PGM3) [9] and ZNF341 [29]. Simultaneously, STAT3-de ciency disease is categorized into two types: STAT3 LOF mutation disease comprises immunode ciencies with syndromic features, while STAT3 GOF mutation disease involves immune dysregulation, especially regulatory T cell defects, according to the International Union of Immunological Societies in 2019 [30]. Our patients overwhelmingly had STAT3 LOF mutations.…”
Section: Discussionmentioning
confidence: 99%
“…A molecular study found that HIES is caused by variations in STAT3, Dedicator of cytokinesis 8 (DOCK8) [28], phosphoglucomutase 3 gene (PGM3) [9] and ZNF341 [29]. Simultaneously, STAT3-de ciency disease is categorized into two types: STAT3 LOF mutation disease comprises immunode ciencies with syndromic features, while STAT3 GOF mutation disease involves immune dysregulation, especially regulatory T cell defects, according to the International Union of Immunological Societies in 2019 [30]. Our patients overwhelmingly had STAT3 LOF mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Accurate and early diagnosis is vital as complement deficiencies and phagocytic disorders are associated with numerous immunological complications. Complement deficiencies cause recurrent and persistent infections in the upper respiratory tract, recurrent pneumococcal and meningococcal infections, hereditary angioedema (HAE), autoimmune complications, and renal failure due to atypical hemolytic uremic syndrome (aHUS) and glomerulonephritis (GN) (8). Severe congenital neutropenia (SCN) and chronic granulomatous disease (CGD) are characterized by low granulocyte counts or defects in the nicotinamide adenine dinucleotide phosphate (NADPH) oxidase pathway, leading to conditions such as delayed wound healing, deep organ infections, and abscess formation.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the disease mechanisms of complement and phagocytic defects that involve the absence, or expression/structural alteration of a functional protein, protein profiling of blood samples could provide a fundamental diagnostic tool (10). Here, we developed a newborn screening assay based on suspension bead array technology for parallel profiling of the main reported disease-associated proteins in the complement cascade, phagocytosis and respiratory burst function (8). The method uses a fraction of DBS corresponding to a sub-microliter volume of blood, and is applicable for population-scale performance (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Primary immunodeficiencies (PIDs) refer to a heterogeneous group of inherited disorders, predominantly caused by single‐gene defects 1 . The American Colonel Bruton is generally considered to have serendipitously discovered the first PID case in 1952, describing agammaglobulinemia as the cause of recurrent pneumonia in an 8‐year old boy 2 .…”
Section: Introductionmentioning
confidence: 99%